Long Term Follow-up of Composite Flaps for Single-stage Reconstruction of Concomitant Tendon and Soft Tissue Defects. Issue 1 (January 2022) - Bekeny, Jenna C.; Zolper, Elizabeth G.; Dekker, Paige K.; Kim, Kevin G.; Wang, Jessica; Nigam, Manas; Attinger, Christopher E.; Fan, Kenneth L.; Evans, Karen K.
Abstract : Background: Tendon rupture in the setting of significant soft tissue loss poses a challenging reconstructive situation, which requires (1) recreating a stable gait cycle, (2) reducing shear forces and re-rupture risk, and (3) providing adequate soft tissue coverage. In this study, we outline our experience with composite flaps in single-step reconstruction of various lower extremity tendinous injuries with soft tissue loss. Methods: A retrospective review of all patients requiring free tissue transfer at our tertiary wound care center between 2011 and 2020 was performed. Patients undergoing single-stage free tissue transfer for both soft tissue coverage and tendon reconstruction were selected. Variables of interest included demographics, comorbid conditions, baseline functionality, reconstructive details, and wound characteristics. Outcomes of interest were flap success, return to ambulation, time to ambulation, and postoperative complications. Results: Nineteen patients were included in this study. Patients were on average 48.0 years old (SD 16.5), with a median Charlson Comorbidity Index of 1.00 (IQR: 0.0–2.5). Defects were most often on the ankle (n = 1 3, 68.4%), with extension to the foot or leg in six of these cases. Median wound size was 68.0 cm 2 (IQR: 48.0–120.0). The most common tendon requiring reconstruction was the Achilles (n = 13, 68.4%). An anterolateral thigh flap with attached fascia lata extension rolled into a neotendon was used in all 19 cases. At baseline, all patients were ambulatory. Only one patient (5.3%) required return to the operating room for suspected vascular compromise. At a median of 14.4 months (IQR: 8.5–40.5), all 19 patients were ambulatory. Conclusions: Simultaneous reconstruction of tendinous injuries and soft tissue defects can be readily achieved via composite free flaps. Although other methods of reconstruction can be considered for smaller soft tissue and tendon loss, this approach has significant utility for patients with large defects and yields robust return to preinjury functionality.